Ecological Niche Modeling of Francisella tularensis Subspecies and Clades in the United States - Nakazawa, Yoshinori (The American Society of Tropical Medicine and Hygiene, 2010)
Two subspecies of Francisella tularensis are recognized: F. tularensis subsp. tularensis (type A) and F. tularensis subsp. holartica (type B). Type A has been subdivided further into A1a, A1b, and A2, which differ geographically and clinically. The aim of this work was to determine whether or not differences among subspecies and clades translate into distinct ecological niches. We used 223 isolates from humans and wildlife representing all six genotypes (type A, B, A1, A2, A1a, or A1b). Ecological-niche models were built independently for each genotype, using the genetic algorithm for rule-set prediction. The resulting models were compared using a non-parametric multivariate analysis-of-variance method. A1 and A2 are ecologically distinct, supporting the previously observed geographic division, whereas ecological niches for types A and B overlapped notably but A1a and A1b displayed no appreciable differences in their ecological niches.